WHAT COULD HAVE BEEN DONE DIFFERENTLY? A PATIENT WITH ACUTE CORONARY SYNDROME - E. P. Panchenko («REMEDIUM GROUP» Ltd., 2016)
A case involving a patient with acute coronary syndrome is described, and a treatment approach is suggested.